Comparative Model of the LinguisticCultural Concept “Motherland” And It’s National-Cultural Conceptual Signs - I.I. Ismatullaeva (Genius Publishing Group, 2023)
This article deals with Comparative model of the linguistic-cultural concept “Motherland”, and it’s national-cultural conceptual signs. The author defines the similarities and differences of the concept “Motherland” with illustrations. When writing this article, various literature and Internet sites were analysed. The comparative method, the method of component analysis of meaning and methods of conceptual analysis were used. In this article, comparative model of the linguistic-cultural concept “Motherland”, and it’s national-cultural conceptual signs was studied and this unit was illustrated with examples.
Keywords: concept; culture; component